A theoretical study of resonance Raman scattering from molecules: High pressure effect - Fujimura, Y. (1980)
The main purpose of this paper has been to study the high pressure effect on the resonance Raman scattering (RRS) of molecules in a dense medium. In deriving the RRS cross section under high pressure, a different approach from that presented in the previous papers has been used, and the resulting expression for the RRS cross section can be used to treat both pressure and temperature effects.